Performance Evaluation of Insulation in 10 kV Switchgear through Partial Discharge Analysis - Dede Furqon Nurjaman; R. Aryo Bimo Surya Putra; Naftalin Winanti; Fauzia Haz; Handoko Rusiana I; Giri Angga Setia; Een Taryana; Ahmad Daelami (Jurusan Teknik Elektro UIN Sunan Gunung Djati Bandung, 2026)
Switchgear acts as the heart of the power distribution and transmission system, namely in the medium voltage system. If the switchgear insulation does not function properly, the risk of interference, equipment damage, and even accidents that endanger human safety can increase. One of the problems that often occurs in insulation is a phenomenon known as partial discharge (PD). PD is an electrical discharge that occurs in the insulating material and is often a sign of damage or defects. Although PD does not always immediately cause failure, if left unchecked, continuous PD activity can damage the insulating material and cause more serious damage. Partial Discharge testing uses a device called Ultra TEV plus 2. The TEV method focuses on measuring transient voltages caused by partial discharges on the surface of an insulator or within electrical equipment. Essentially, PD emits electrical signals that can be measured as voltage changes. Meanwhile, with the ultrasound method, ultrasonic sensors are installed near the electrical equipment being monitored. When PD occurs, the sensors capture the ultrasonic waves produced and convert them into signals that can be further analyzed. After measurements are taken using the TEV and Ultrasound methods, the results are compared with standard TEV values. It was found that a moderate level of internal PD is likely to occur at the measurement locations of the upper busbar and the CT compartment of Cubicle 10BBC08, as well as the R, S, T phase cables of Cubicle 10BBC09. A high level of internal PD is likely to occur at the measurement locations C2, C3, and C5 on the Bus duct of Cubicle 10BBC10.